Analysis of Application of Coaching Techniques in the Project of Strengthening Pancasila Student Profiles in Indonesian Lessons in SMP - Wulandari, Septi; Kuntarto, Eko; Rally, Handayani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the suitability of coaching learning techniques to implement the Pancasila student profile strengthening project in Indonesian subjects at SMPN 1 Muara Bungo. The theme of a sustainable lifestyle with the topic of sustainable tourism was chosen because Muara Bungo Regency has tourism objects and potential for environmental-based tourism. This research is development research using the Borg & Gall development model and adapted to the coaching technique and the Guide to the Development of Pancasila Student Profile Strengthening Projects published by the Education Standards, Curriculum and Assessment Agency, Ministry of Education, Culture, Research and Technology of the Republic of Indonesia. The results of the study found that the coaching technique was suitable to be applied in extracurricular activities of the Pancasila student profile strengthening project in Indonesian subjects for persuasive speech material. Because it met the principles of implementing P5, namely; holistic, contextual, learner-centered, and exploratory.